PERSEPSI MASYARAKAT MELAYU PETALANGAN TERHADAP PERGESERAN NILAI RELIGIUSITAS BUDAYA MANSI BALIMAU (STUDI DI DESA RAWANG EMPAT BANDAR PETALANGAN KABUPATEN PEALAWAN) - Kasiroh "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Sense of joy with the arrival of Ramadan ekspressed various ways by Malay Petalangan community in various ways, one way to clean themselves with bath known as balimau. Mandi balimau held once a year, a day before the holy month of Ramadan or month of this traditional .Ceremony than as an expression of gratitude and excitement into the month of fasting, is also a symbol of purification and self-cleaning. Balimau itself means a bath using water mixed with orange by the local people called limes. Now, There are worries us together, that customary such pretty packed ninik mamak and indigenous stakeholders ,, slowly there has been a shift in values, it can be seen with the naked eye the intermingling of men and women who are not mahram in one bath / river, frivolous, redundant, inconsiderate highway, even leads to sin. Of course this is contrary to the values of eastern culture and religious norms. The purpose of the study was to determine the perception and the public response to the Malay community Bandar Petalangan shift in values religiosity balimau bathing culture. As well as to analyze the factors that cause changes in the value of the balimau bathing culture to people's social life.The results showed that Bath Balimau trusted by the community, especially the Malay Petalangan Rawang Empat villages as a way to purify themselves before entering the holy month of Ramadan, participants bath Balimau no age restrictions. Rank, position, men, women, children or adults, anyone can do it, before carrying out the process bath Balimau Village community Rawang Empat usually do grave pilgrimage, organized study groups, wirid Yaseen and a celebration or festivity as gratitude towards Allah SWT. Then the change is caused by several factors including, mindset which began advanced, heterogeneous population, influence and cultural contacts outside and Adaiah sense of dissatisfaction within the community itself.Keywords: Bath Balimau, Perception, Changes